Ghosting : a love story - Skilton, Tash (Kensington Books, 2020)
"Dumped by his fiancée, not only is Miles couch-surfing across New York City, but downsizing has forced him to set up shop at a café. Also, he no longer believes in love. Not a good look in his line of work . . . Do not present a "perfect" image. No one will trust it. Nor should they. Zoey's eccentric L.A. boss sent her packing to New York to "grow." But beneath her chill Cali demeanor, Zoey's terrified to venture beyond the café across the street . . . Think of your quirks - such as cosplaying B-movies from the 1980s-as a "Future Honesty." Save these as a reward only for those who prove worthy. The only thing Miles and Zoey share is their daily battle for Café Crudite's last day-old biscotti. They don't know they're both ghostwriting "authentic" client profiles for rival online dating services. Nope, they have absolutely nothing in common. . . . Until they meet anonymously online, texting on the clock."--Publisher.